Haematology and Serum Biochemistry of Rams Fed Developed Total Mixed Rations Formulated Agricultural Waste Using Value Addition Science Technology (VAST). - Kolo, U.M.; Girgiri, A.Y.; Asheikh, L.G; Modu-kagu, H.A.; Abbator, F.I.; Mustapha, M.; Danbaki, A.A.; Mohammed, I.D. (Nigerian Journal of Animal Science, 2026)
The study is aimed to evaluate the effect developed total mixed rations formulated agricultural waste using value addition science technology (VAST) on for a period of 84 days. A total of twenty-five (25) fattening rams were used for this study. The Rams randomly assigned to five treatments of five rams each. The fed developed total mixed rations formulated as T1, T2, T3, T4 and T5 for a period of 84 days The amount of feed that was offered minus the amount that was refused was used to calculate feed intake. Ad libitum water was provided. At the end of the experiment, three (3) animals from each treatment were selected and fasted. There were no significant (P>0.05) differences among the treatments for Packed Cell Volume (PCV), Haemoglobin (Hb), Red Blood Cell value (RBC), White Blood Cell count (WBC), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin Concentration (MCHC) and White Blood Cell differential (all the parameters measured were within the reference values). The Direct Bilirubin, Conjugated Bilirubin, Albumin, Globulin, Cholesterol, blood urea, Aspartate Aminotransferase (AST), Alanine Aminotransferase, Alkaline phosphatase were significantly (P<0.05) different among the treatment groups. However, Total protein, Glucose, and Creatinine were not statistically (P>0.05) different among the treatment groups. Therefore, the study suggests that using agricultural waste-based total mixed rations formulated using value addition science technology is a viable option for feeding ruminants, as it does not have any adverse effects on the hematological and serum biochemical parameters of the animals.